2011
DOI: 10.1002/jor.21373
|View full text |Cite
|
Sign up to set email alerts
|

The effects of multiple freeze–thaw cycles on the biomechanical properties of the human bone‐patellar tendon‐bone allograft

Abstract: Introduction: Soft tissue allografts, such as the bone-patellar tendon-bone (BPTB) graft, have been frequently used for anterior cruciate ligament (ACL) reconstruction. As allografts are subjected to freezing and thawing for multiple cycles, the objective of this study was to measure the changes of the biomechanical properties of the human BPTB allograft after 4 and 8 freeze–thaw cycles in comparison to a single freeze–thaw cycle. Methods: Three BPTB specimens were procured from 21 human donors and divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 26 publications
4
76
1
3
Order By: Relevance
“…The material parameters, stress, and modulus were unaffected by increasing freeze-thaw cycles or even by freeze-drying. These results are in line with those of other authors regarding soft tissue [6,8,9] and hard tissue [10,13,14] as a result of freezing and thawing cycles. Two previous studies [12,17] found that processing and storage caused freeze-dried allograft bone to be weaker, but we did not compare our samples with the same control group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The material parameters, stress, and modulus were unaffected by increasing freeze-thaw cycles or even by freeze-drying. These results are in line with those of other authors regarding soft tissue [6,8,9] and hard tissue [10,13,14] as a result of freezing and thawing cycles. Two previous studies [12,17] found that processing and storage caused freeze-dried allograft bone to be weaker, but we did not compare our samples with the same control group.…”
Section: Discussionsupporting
confidence: 93%
“…These specific treatments were chosen to span the range between the minimum and maximum cycles expected to be encountered by graft material between recovery and use. The maximum number of eight freeze-thaw cycles was chosen by consultation with American Association of Tissue Banks [1] and other published data [6]. Each treatment was represented once within a donor, thus each treatment had an n = 18.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As radiografias foram avaliadas quanto a doença óssea ou nutricional, fraturas da crista da tíbia, sinais de artroplastia ou osteotomia da tuberosidade da tíbia. Após remoção de tecidos moles estas foram armazenadas em freezer convencional, com temperatura de -20° Celsius (PARK et al, 2009;GOH et al, 2010;JUNG et al, 2011). As peças foram armazenadas em embalagens plásticas com dimensões de 50 centímetros de altura e 30 centímetros de largura.…”
Section: Limitações Do Estudounclassified
“…(JUNG et al, 2011). Esta temperatura foi baseada em estudos similares previamente realizados (DENNLER et al, 2006;KOWALESKY;LINS et al, 2009;PARK et al, 2009;ETCHEPAREBORDE et al, 2010;GOH et al, 2010;BUTLER et al, 2011;JUNG et al, 2011 DOVERSPIKE et al, 1993;DUPUIS et al, 1994;CHAUVET et al, 1996;BONFIM;PACCOLA, 2000;INNES et al, 2000;MORRIS;LIPOWITZ, 2001;BOUDRIEAU, 2005;CONZEMIUS et al, 2005;DAMUR, 2005;HOFFMANN et al, 2006;BARAÚNA et al, 2007;TARTARUNAS et al, 2007;STEINS;SCHMOEKEL, 2008;VOSS, et al, 2008;GUERRERO et al, 2009;DYMOND;GOLDSMID;SIMPSON, 2010;BISGARD et al, 2011;KEMPER et al, 2011;STEINBERG et al, 2011).…”
Section: Dispositivo Para Corpo De Provaunclassified